Aplikasi Teknologi Floating Catfish Pellet Sebagai Solusi Pemanfaatan Larva Black Soldier Fly di Mitra Usaha Mazgot BSF Boyolali - Agung Budiharjo; Adi Magna Patriadi Nuhriawangsa; Lilik Retna Kartikasari; Bayu Setya Hertanto (PRIMA: Journal of Community Empowering and Services, 2022)
Application of Floating Catfish Pellet Technology as a Solution for Utilizing Black Soldier Fly Larvae at Mazgot BSF Boyolali Business Partners. The black soldier fly (BSF) raised by a business partner Mazgot BSF Boyolali is an effort that exists to solve the problem of organic waste. However, the high production of BSF maggots has become a challenge for partners to find alternative ways to take advantage of the maggot. The application of feed technology based on BSF maggot can increase business productivity because BSF raising is not only aid for overcoming the problem of organic waste, but it can be used as a source of feed ingredients as well. The purpose of the service activity is to provide assistance in the application of fish pellet feed technology (floating fish pellet) as a solution to the use of BSF maggot. This activity was conducted by giving a mentoring of feed technology application based on BSF maggots including selection of raw feed materials, feed processing, and physical measurement of feed as well. The result of this activity showed that partners are able to formulate fish pellet based on available feed ingredients approach to the chemical content of feed ingredients and fish nutrient needs. The content of fish feed has complied with the SNI for catfish feed including crude protein 35.25%; crude fat 13.94%; crude fiber 6.37%; ash 11.43%; BETN 26.26%; and 1409.58 kcal/kg energy. The resulting physical quality is also categorized as good including buoyancy reaching 1 – 2 hours and good stability.